2014
DOI: 10.4018/ijvple.2014040104
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Interactive Immersion Environment for Engendering Understanding about Nanotechnology

Abstract: The advent of nanoscientific applications in modern life is swiftly in progress. Nanoscale innovation comes with the pressing need to provide citizens and learners with scientific knowledge for judging the societal impact of nanotechnology. In rising to the challenge, this paper reports the developmental phase of a research agenda concerned with building and investigating a virtual environment for communicating nano-ideas. Methods involved elucidating core nano-principles through two purposefully contrasting n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The inevitable impact of nano on society requires international citizens to be able to make scientifically-based judgments about associated perceived benefits, risks, hopes and fears (Roco and Bainbridge, 2005;Waldron et al, 2006;Schütz and Wiedemann, 2008). This premise is also closely intertwined with the mandate of science education in disciplines such as chemistry and biology education where it is becoming increasingly necessary to connect core discipline based concepts to the nanoscale in preparation of the modern learner (Muniz and Oliver-Hoyo, 2014;Orgill and Wood, 2014;Schönborn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The inevitable impact of nano on society requires international citizens to be able to make scientifically-based judgments about associated perceived benefits, risks, hopes and fears (Roco and Bainbridge, 2005;Waldron et al, 2006;Schütz and Wiedemann, 2008). This premise is also closely intertwined with the mandate of science education in disciplines such as chemistry and biology education where it is becoming increasingly necessary to connect core discipline based concepts to the nanoscale in preparation of the modern learner (Muniz and Oliver-Hoyo, 2014;Orgill and Wood, 2014;Schönborn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation resulted in effective head tracking. Visitors perceived the nanotubes as protruding from the screen and they often moved around to view the nanotubes from other angles or to simply experience the motion parallax [6]. They could also simultaneously grasp nanotubes with both hands (Figure 3).…”
Section: An Interactive Simulation Of the Nanoworldmentioning
confidence: 99%
“…In previous work [6] we have shown that users of the NanoSim system have an immersive experience and that the system stimulates interaction with and learning about nanophenomena. By engaging the three components of exploranation, we have observed how the "confluence of exploration and explanation" [5] is directly observable from users' interaction with NanoSim.…”
Section: Exploranative Learning Events With Nanosimmentioning
confidence: 99%
“…Recently, logging has been applied to research contexts where real-time As curators and pedagogues aim to pursue the communicative and potential educational benefits of museum and science center environments in the digital age, increasing research attention is on measuring aspects such as attraction, engagement, holding power and dwell time of interactive exhibits [9][10][11][12]. Another developing area is probing how visitors actually use and interact with the digital platforms, and what the nature of interaction may eventually imply for learning [5,7,13].…”
Section: Research On Interactive Multi-touch Tables In Science Centermentioning
confidence: 99%
“…Recent research indicates that interactions afforded by modern technologies play a critical and highly relevant role in scientific meaning-making [4]. Moreover, recent work [5][6][7] also shows that analytical tools that track and log users' behavioural interactions can produce fine-grained information about how bodily processes of interaction could map onto processes of engagement and learning.…”
Section: Introductionmentioning
confidence: 99%